PENGARUH METODE PROBING PROMTING PENGARUH METODE PROBING PROMTING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SMA NEGERI 17 SURABAYA: PENGARUH METODE PROBING PROMTING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SMA NEGERI 17 SURABAYA - Hidayah, Miftakhul; Listyaningsih, Listyaningsih (Kajian Moral dan Kewarganegaraan, 2023)
This study aims to examine the effect of applying the Probing Prompting method to student learning outcomes. This type of research is Quasy experiment with Nonequivalent Control Group Design. From a population of 319 students, samples were obtained using the cluster random sampling method, consisting of 70 respondents from class X-3 as the control group and X-9 as the experimental group. The research data was obtained by administering multiple choice tests pretest and posttest. The learning outcomes referred to are cognitive aspects with a focus on Higher Order Thinking Skills. Data analysis was carried out using IBM SPSS Statistics version 26. This study used the Mann-Whitney Non-parametric t test with the result Asymp.Sing (2 - tailed) 0.029 <0.05, so the hypothesis was accepted. Thus it can be concluded that there is an influence of the Probing Promting learning method on student learning outcomes in class X Pancasila Education at SMA Negeri 17 Surabaya. The influence of the Probing Promting method in this study was 0.51.